Avaliação do polimorfismo da metilenotetraidrofolato redutase (MTHFR) em amostras de câncer colorretal e câncer de mama - Alessandra Duarte Clarizia (2006)
Epidemiologic studies suggest that the methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism may modify the risk of both colorectal cancer (CRC) and breast cancer (BC). The C677T polymorphism is associated with the expression of a thermolabile enzyme with decreased activity that influences the levels of methyl-donor molecules. Considering that methylation abnormalities appear to be important in the pathogenesis of CRC, we have examined the relationship between the genotype at the MTHFR C677T polymorphism, hypermethylation of the promoter region of five genes (DAPK, MGMT, hMLH1, INK4a ARFp16 and p14 ) and microsatellite instability (MSI) in 106 patients with CCR. In 195 BC cases, the genotype C677T was correlated with clinical parameters of the patients and stage of disease. The MTHFR C677T polymorphism was assessed by using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The analysis of MTHFR 677 TT genotype between cases and controls did not reveal any statistically significant difference. We did not show statistically significant differences in the genotypic frequencies of the MTHFR C677T polymorphism with or without hypermethylation of one or multiple loci. However, our study found a significant excess of 677TT individuals among patients with CRC with MSI. This strong association appears to be independent of the methylation status of hMLH1 or of the biogeographical genomic ancestry of the patients (typed utilizing indels). An explanation for this mechanism between MSI, 677TT genotype and CCR is not clear. We did not find statistical difference in the frequency of 677 TT genotype between controls and BC cases. In BC patients, no frequency differences of 677 TT genotype were observed among smoking habit, age, and menopausal status at the initial diagnosis. However, a strong statistical association was found between TT genotype and BC alcohol drinkers and BC stage IIIA. Our results suggest that the low activity of the MTHFR, and the powerful folate antagonistic action of alcohol, could increase the risk for BC. Besides the association between severity of disease and TT genotype, in this study, BC stage is linked to temporality of diagnosis and does not reflect tumor aggressiveness. Additional studies should be carried out to clarify the relationship among alcohol drinking, stage, and. MTHFR C677T polymorphism. The preventive use of folate for BC drinkers, bearing 677 TT genotype, may be considered to reverse the effect of